1992
DOI: 10.1111/j.1365-2958.1992.tb02201.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Escherichia coliβ‐galactosidase in Mycobacterium bovis BCG using an expression system isolated from Mycobacterium paratuberculosis which induced humoral and cellular immune responses

Abstract: A promoter sequence, PAN, was isolated from Mycobacterium paratuberculosis and characterized. This promoter lies adjacent to, and outside, the 3' end of an IS900 insertion element. IS900 contains an open reading frame, ORF2, on the complementary strand which codes for the putative transposase of this insertion sequence. A DNA fragment containing PAN and part of ORF2 was fused to the lacZ gene and inserted into the replicative shuttle vector pRR3. Mycobacterium smegmatis and Mycobacterium bovis BCG (BCG) transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 26 publications
(10 reference statements)
1
57
1
Order By: Relevance
“…The experiment was therefore performed using RNA isolated from M. smegmatis cells harbouring various katG promoter clones. The determination of transcription start sites for M. tuberculosis genes, using this heterologous host, has been shown to correlate well with results obtained from native mRNA transcripts (Levin & Hatfull, 1993 ;Dhandayuthapani et al, 1997 ;Movahedzadeh et al, 1997), and has successfully been used as a substitute in many cases (Murray et al, 1992 ;Kremer et al, 1995 ;Nesbit et al, 1995).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The experiment was therefore performed using RNA isolated from M. smegmatis cells harbouring various katG promoter clones. The determination of transcription start sites for M. tuberculosis genes, using this heterologous host, has been shown to correlate well with results obtained from native mRNA transcripts (Levin & Hatfull, 1993 ;Dhandayuthapani et al, 1997 ;Movahedzadeh et al, 1997), and has successfully been used as a substitute in many cases (Murray et al, 1992 ;Kremer et al, 1995 ;Nesbit et al, 1995).…”
Section: Discussionmentioning
confidence: 67%
“…2. The construct pANIIIW (a gift from Karen Kempsall, Glaxo-Wellcome), consisting of a 170 bp PCR fragment containing the P AN promoter cloned into the T-tailed EcoRV restriction site of the vector pT7Blue (Novagen), was used as a source of the M. paratuberculosis promoter (Murray et al, 1992). The 218 bp HindIII-BamHI fragment from pANIIIW was cloned into the corresponding restriction sites of pJCluc to form pLPan.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the promoter P AN of M. paratuberculosis [43] subunit of pertussis toxin [30]. Our results showed that, contrary to DTP, the response to the rBCGpUS977dtbpw8 was strong, especially in the 12 -20 week interval.…”
Section: Discussionmentioning
confidence: 59%
“…Our best results came out with the BCG transformed with the pUS977dtb PW8 construct in which the expression of DTB is driven by the P AN promoter, a regulatory sequence derived from M. paratuberculosis. The P AN sequence, a weak mycobacterial promoter [18], has been successfully used by others for the expression of the α-galactosidade of E. coli [30], the LacZ of E. coli [31], the Gp63 surface antigen of Leishmania [32], the Nef antigen of Simian Immunodeficiency Virus [33], the Nef, Gag, Env antigens of Simian Immunodeficiency Virus [34], the S1 subunit of the Bordetella pertussis toxin [24], the hepatitis B surface antigens [35] and the LipL32 antigen of Leptospira interrogans [28]. In our study all rBCGpUS977dtb PW8 clones stably expressed significant amounts of DTB while rBCGpUS973dtb PW8 clones were unstable and, consequently, unsuitable for DTB expression.…”
Section: Discussionmentioning
confidence: 99%